2004
DOI: 10.1099/vir.0.80344-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of white spot syndrome virus within Vietnam

Abstract: White spot syndrome virus (WSSV), the sole member of the virus family Nimaviridae, is a large double-stranded DNA virus that infects shrimp and other crustaceans. By alignment of three completely sequenced isolates originating from Taiwan (WSSV-TW), China (WSSV-CN) and Thailand (WSSV-TH), the variable loci in the genome were mapped. The variation suggests the spread of WSSV from a common ancestor originating from either side of the Taiwan Strait to Thailand, but support for this hypothesis through analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
157
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(171 citation statements)
references
References 29 publications
9
157
2
3
Order By: Relevance
“…Similar analysis of the ORF14/15 and ORF23/24 variable regions in 81 WSSV isolates from India showed them to be the major polymorphic loci, and indicated that the Indian isolates were likely to have originated from Thailand (Pradeep et al 2008). Another study demonstrated that variable-number tandem-repeat (VNTR) sequences in ORF75 and ORF125 were also useful markers for examining interregional spread of WSSV (Dieu et al 2004.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Similar analysis of the ORF14/15 and ORF23/24 variable regions in 81 WSSV isolates from India showed them to be the major polymorphic loci, and indicated that the Indian isolates were likely to have originated from Thailand (Pradeep et al 2008). Another study demonstrated that variable-number tandem-repeat (VNTR) sequences in ORF75 and ORF125 were also useful markers for examining interregional spread of WSSV (Dieu et al 2004.…”
Section: Introductionmentioning
confidence: 75%
“…Although overall nucleotide sequence identity amongst the 3 genomes is high (99.32%), single nucleotide mutations and deletions/insertions, a variable region prone to recombination, variation in the number of repeat units within hrs and direct repeats, a 13 kb deletion in WSSV-TH and a transposase sequence unique to WSSV-TW were identified in genome-sequenced comparisons ). Some of the loci displaying variability have been exploited as epidemiological tools to track the spread of WSSV in shrimp farmed in Vietnam (Dieu et al 2004). From the data, it was evident that the WSSV types that emerged in Vietnam shared a common lineage with Thai WSSV types, had digressed from lineages found in Taiwan and China, and were likely to have been derived from multiple introduction events.…”
Section: Introductionmentioning
confidence: 89%
“…Determining VNTR numbers/types and ORF14/15 and ORF23/24 indel types of WSSV strains has provided insights into WSSV epidemiology (Dieu et al 2004, Pradeep et al 2008, Walker et al 2011a. Of the 3 VNTR loci, ORF94 has proved to be the most informative single genetic marker for delineating WSSV strains (Wongteerasupaya et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This region shows more variation, with a wide range of compound repeat units (RUs) between the WSSV isolates originating from farming and wild hosts (Wongteerasupaya et al, 2003;Dieu et al, 2004;Musthaq et al, 2006;Pradeep et al, 2008;John et al, 2010;González-Galaviz et al, 2013). Several studies have suggested a correlation between the RUs of ORF94 and WSSV virulence as follows: the fewer RUs (<9) the higher mortality rate in shrimps (Waikhom et al, 2006;Pradeep et al, 2008;Hoa et al, 2012).…”
mentioning
confidence: 99%
“…A study in Thailand revealed the presence of different genotypes with a range of 6-20RUs, where 8 RUs was the most frequent (Wongteerasupaya et al, 2003). In two ORF94 studies in Vietnam, the number of RUs varied (Dieu et al, 2004) and 4-17 RUs (Dieu et al, 2010), the former was performed using samples from eight localities from central and southern regions, while the latter was performed using samples from nine localities in the northern, central and southern part of the country. In India¸ the genomic analysis included 513 samples from 13 localities, showing genotypes with a range of 2-16RUs, where genotypes with <8 RUs were predominant during the outbreak periods and genotypes with >9 RUs were more frequent in the nonoutbreak periods (Pradeep et al, 2008).…”
mentioning
confidence: 99%